ANALYSIS MODEL SERVANT LEADERSHIP, FLEXIBLE WORK ARRANGEMENTS, AND ORGANIZATIONAL CLIMATE IN PREDICTING EMPLOYEE RETENTION: CASE STUDY ON THE BANKING SECTOR - Reina A. Hadikusumo; Raden Isma Anggraini; Yuliana Yuliana; Zain Ashfaq (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2026)
The high level of employee turnover in the banking sector amidst the dynamics of organizational transformation and changes in work patterns requires companies to develop more adaptive and sustainable retention strategies. Although various studies have identified factors that influence employee retention, studies that integrate servant leadership, flexible work arrangements, and organizational climate in one empirical model are still relatively limited, especially in the context of the banking industry. This research aims to analyze the influence of servant leadership, flexible work arrangements, and organizational climate on employee retention in the banking sector. The research used a quantitative approach with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method, with 200 banking employees as respondents. The research results show that servant leadership has a positive and significant effect on employee retention through increasing employee trust, involvement and organizational commitment. Flexible work arrangements have been proven to improve work-life balance and job satisfaction which has an impact on increasing employee intentions to remain in the organization. Apart from that, a conducive organizational climate plays a significant role in strengthening employee loyalty and attachment to the company. Simultaneously, these three variables provide a substantive contribution in explaining employee retention in the banking sector. This research contributes theoretically in expanding the perspective of organizational behavior related to employee retention and provides practical implications for banking management in designing servant leadership, flexible work systems, and organizational climates that support the sustainability of human resources.